2017
DOI: 10.3892/ol.2017.6890
|View full text |Cite
|
Sign up to set email alerts
|

Adenine causes cell cycle arrest and autophagy of chronic myelogenous leukemia K562 cells via AMP-activated protein kinase signaling

Abstract: Abstract. AMP-activated protein kinase (AMPK) is known as a pivotal regulator of cellular metabolism. Mounting evidences have demonstrated that AMPK activation exerts tumor suppressive activity on leukemia cells. The present study reported that adenine, an AMPK activator, triggers cell cycle arrest and autophagy of human chronic myelogenous leukemia K562 cells consequently suppressing cell viability. The present findings revealed that adenine treatment (4.0-8.0 mM) significantly inhibited the viability of K562… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 32 publications
2
18
0
Order By: Relevance
“…In contrast, supplementing the diet of adult APRT mutants with adenine, restored the AMP : ATP ratio to that of control flies and abolished the effect on longevity. As the authors note, these results are counterintuitive to the mutations, and are in direct contrast to the results obtained in human cell models . Although, as assessed in the section on ADSL and AdSS, this surprising result might be explained by assuming a peculiar adenine nucleotide metabolism in Drosophila , it is impossible to apply these results to the set‐up of potential therapeutic and dietary interventions that may extend the lifespan and improve the health span of humans.…”
Section: Enzymes Participating In Adenylate Metabolismmentioning
confidence: 81%
“…In contrast, supplementing the diet of adult APRT mutants with adenine, restored the AMP : ATP ratio to that of control flies and abolished the effect on longevity. As the authors note, these results are counterintuitive to the mutations, and are in direct contrast to the results obtained in human cell models . Although, as assessed in the section on ADSL and AdSS, this surprising result might be explained by assuming a peculiar adenine nucleotide metabolism in Drosophila , it is impossible to apply these results to the set‐up of potential therapeutic and dietary interventions that may extend the lifespan and improve the health span of humans.…”
Section: Enzymes Participating In Adenylate Metabolismmentioning
confidence: 81%
“…A number of previous studies demonstrated that cell cycle arrest and apoptosis may be directly associated (32)(33)(34). For instance, the apoptotic cascade may be inhibited or induced via cell cycle manipulation depending on the cellular circumstance (35).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to energy regulation, AMPK also governs the important cellular physiological activities including cell proliferation, cell growth, and autophagy (18,19). Accordingly, AMPK has been recognized as an important anticancer target in suppressing the growth of different carcinoma cells such as 786-O (10), K562 (11), and HT29 (20). Similarly, we also observe that adenine-induced AMPK activation play an important role in the growth inhibition of HepG2 and SK-Hep-1 cells which express wild-type p53.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have demonstrated that adenine exerts its anticancer activity by activating AMPK and the associating signaling (10,11). As a result, the role of AMPK activation in adenineinduced apoptotic signals in HepG2 cells was then investigated.…”
Section: Adenine Induced Activation Of Ampk To Trigger P53-mediated Amentioning
confidence: 99%
See 1 more Smart Citation